“Definite Associative Deixis”: Between Referential and Attributive Readings - Jan Dvořák (Discours)
This paper investigates different readings of definite descriptions within “definite associative deixis”. The term itself was proposed in Dvořák (2023) to refer to Hawkins’ “larger situation uses based on general knowledge” (1978). The terminological choice is grounded in an analogy between the phenomenon under investigation and definite associative anaphora since in both cases, the head noun of the definite description is a functional concept (Löbner, 2011) calling for a contextual argument. What changes is the source of this argument (anchor). While in cases of definite associative anaphora, the contextual argument is provided by discourse, as far as “definite associative deixis” is concerned, it is provided by the situation of utterance. In the present study, we argue that within a particular situational framework, one and the same associative deictic description is prone to be interpreted either in a referential or in a non-referential, i.e. “attributive”, fashion (Donnellan, 1966). We also attempt to show how this discrepancy in terms of referentiality builds on the unequal access that the speaker and the hearer have to a particular extralinguistic reality. In certain situations, more than one account of the functioning of the associative deictic description seems acceptable. Hence, the question of whether we are dealing with a referential or an attributive use remains open.